Observation of B+c→D0K+ decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2017)
Using proton-proton collision data corresponding to an integrated luminosity of 3.0 fb−1, recorded by the LHCb detector at center-of-mass energies of 7 and 8 TeV, the B+c→D0K+ decay is observed with a statistical significance of 5.1 standard deviations. By normalizing to B+→¯D0π+ decays, a measurement of the branching fraction multiplied by the production rates for B+c relative to B+ mesons in the LHCb acceptance is obtained, RD0K=(fc/fu)×B(B+c→D0K+)=(9.3+2.8−2.5±0.6)×10−7, where the first uncertainty is statistical and the second is systematic. This decay is expected to proceed predominantly through weak annihilation and penguin amplitudes, and is the first B+c decay of this nature to be observed.